PENGEMBANGAN APLIKASI LENGO KIDS (LANGUAGE FOR KIDS) UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN ANAK USIA 5-6 TAHUN - Tasya, Nanda; Kurnia, Rita; Satria, Defni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to develop and evaluate the feasibility of an interactive digital learning media, the LENGO Kids application, to address the need for engaging reading tools and improve the early reading skills of children aged 5-6 years. This study utilized the Research and Development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. Data collection techniques included observation, interviews, and expert validation questionnaires measured using a Likert scale. The limited trial subjects consisted of six children aged 5-6 years at TK Mutmainnah Dayun. The validation results showed that the LENGO Kids application is highly feasible, with a feasibility percentage of 90% from material experts, 91% from media experts, and 93% from educational practitioners. During the limited trial implementation phase, the practicality response reached 92%. In conclusion, the LENGO Kids application, which integrates visual and audio approaches with the local Malay Riau culture, is proven to be highly feasible and practical as an innovative medium to stimulate letter, syllable, and simple sentence recognition skills in early childhood.